Maximizing the Skills of Bringing Student Events Through the Use of Youtube - Siti Ulfiyani (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2020)
The background of the research is the importance for the students to have master of ceremony skill. Therefore, appropriate alternative learning concept needs to be formulated to help the students to optimize the skill to be a master of ceremony. This study aims to describe Youtube as an alternative learning. This research uses a qualitative approach with descriptive methods. Data collection techniques using literature study and observation. The instruments used were data cards and observation guidelines that had been validated by experts. The study was conducted in 2019 with informants of Indonesian Language Education Study Program students at the University of PGRI Semarang who took the Speaking Course. Data validity uses the triangulation of data sources. The data collected was analyzed using stages: classification, analysis, and drawing conclusions. The  results showed that Youtube can be used as a source of learning, learning media, and a means of disciplining learning products. With the right form of utilization, Youtube can minimize various obstacles, including limited time for practice, students' oral language skills, and knowledge possessed by students.